A study on factors influencing use of standard precautions in the emergency department at BPKIHS, Dharan - Aryal, Bijaya Devi; Rai, B K; Gupta, P P; Giri, S; Chaudhuri, S; Yadav, A K (Health Renaissance, 2017)
Background: This study investigated knowledge of and practices towards standard precautions, among all health care workers working in the emergency department in BPKIHS. Objective: To find out the factors influencing use of standard precautions in the emergency department, BPKIHS Dharan. Methods: This was a prospective observational study conducted in the emergency department. Data was collected in three ways: by direct observation of work practice, a questionnaire about knowledge, attitude and skills and through focus group discussions. Results: Regarding standard precaution, majority (54.2%) had partial knowledge. Only 4.2% know the component of it. In practice 69.52% among doctors group washed hand even though once in four observations; 96% used soap. 43.80% used gloves in doctors group in four observation; sisters used gloves the entire times. 74% washed hand after gloves removal (178). 35.23% didn’t recapped needles before disposal from those who used it among doctors group. Recapping is complete in sisters’ group. 60.95%. Sisters had complete proper disposal practice. Conclusion: Knowledge and practice of SP has direct impact in health of patient and HCW. High level of occupational exposure to blood highlights the urgent need for intervention to enhance occupational safety to prevent unnecessary nosocomial transmission of BBD. Strategies for promoting injection safety are necessary if the risk of nosocomial transmission of BBV via unsafe injection practice is to be minimized. Health Renaissance 2015;13 (3): 54-64